ESTRUCTURA Y COMPOSICIÓN DE LA COMUNIDAD DE MACRO INVERTEBRADOS ACUÁTICOS ASOCIADOS A TILLANDSIA TURNERI BAKER (BROMELIACEAE) EN UN BOSQUE ALTO ANDINO COLOMBIANO - Ospina-Bautista, Fabiola; Estévez-Varón, Jaime V.; Betancur, Julio; Realpe-Rebolledo, Emilio (Instituto de Ecología, A.C., 2004)
We studied the acuatic macro invertebrates community associated with the water tank of Tillandsia turneri (Bromeliaceae) in a montane cloud forest (at 3000 m altitude) of Cundinamarca, Colombia. Thirty seven plants were sampled for which the amount of water and some morphological and physicochemical variables were also determined. Twenty eight of macro invertebrates morphospecies were found, 20 of which were Diptera. The order Coleoptera was the most abundant, with 40.5% of the total number of individuals, followed by Diptera and Cladocera, each with approximately 25% of the total individuals. Shannon´s diversity index for each plant was between 0.735 and 2.133, and Margalef’s richness index was between 1.249 and 3.246. Using a similitud analysis a group of 20 individuals of T. turneri with a similar composition of macro invertebrates was identified. The most abundant functional groups were shredders-piercers represented by the genus Scirtes and collectors-filterers represented by the families Culicidae and Daphnidae. The physicochemical and morphological variables were not related with species richness and diversity of the macro invertebrates community. However, multiple regression for macro invertebrate abundance was significtive, showing that the plant area and the amount of water were the variables that better explained it. Too, the multiple regression indicates that the abundance of Haemagogus and Tanyponinae sp. 1 was explained for the amount water in the plant tank.